2020
DOI: 10.33233/fb.v21i1.3625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incentive spirometry after cardiac surgery: protocol for a systematic review

Abstract: Introduction: Patients receiving cardiac surgeries present high risk of developing postoperative complications. Incentive spirometry (IS) is used for the prevention and treatment of postoperative pulmonary complications in patients undergoing cardiac surgeries. Publications have suggested that IS is ineffective. In contrast, some studies have shown that when IS is adequately used, it may lead to beneficial outcomes. Objectives: To assess the effect of IS in patients undergoing cardiac surgeries. Methods/design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With respect to the secondary outcomes analysis, four trials reported LOS [ 33 , 40 , 43 , 45 ] , two reported ICU LOS [ 36 , 43 ] , eight reported parameters of lung function [ 24 , 29 , 30 , 33 , 34 , 36 , 41 , 47 ] , ten reported PaO 2 , nine reported SO 2 , and one reported reintubation rate. No trials evaluated the use of antibiotics (which was an outcome of interest for this review [ 16 ] ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the secondary outcomes analysis, four trials reported LOS [ 33 , 40 , 43 , 45 ] , two reported ICU LOS [ 36 , 43 ] , eight reported parameters of lung function [ 24 , 29 , 30 , 33 , 34 , 36 , 41 , 47 ] , ten reported PaO 2 , nine reported SO 2 , and one reported reintubation rate. No trials evaluated the use of antibiotics (which was an outcome of interest for this review [ 16 ] ).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a systematic review following the reporting recommendations proposed by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (or PRISMA) [ 15 ] . The protocol was registered in the International Prospective Register of Systematic Reviews (or PROSPERO) (#CRD42020161009), is available online at https://www.crd.york.ac.uk/prospero/export_record_pdf.php ), and was previously published [ 16 ] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation